Impact of Remote Work on Software Teams: A Qualitative Study - Menolli, André; Coleti, Thiago A.; Morandini, Marcelo (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES); 2023: Anais do VIII Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software, 2023)
The COVID-19 pandemic introduced a new scenario to several software companies, which were forced to adopt home office work. The new situation imposed by the COVID-19 pandemic presents several challenges for companies, particularly in how they manage development teams and the knowledge produced. This work focuses on understanding the main modifications in software development teams when changing their work mechanisms from face-to-face to remote. A study through interviews was performed and qualitative data analysis was carried out. The results show that remote work brought both advantages and disadvantages compared to face-to-face work. Furthermore, companies with well-defined processes had less difficulty adapting to remote work.